Long-term maternal intake of inulin exacerbated the intestinal damage and inflammation of offspring rats in a DSS-induced colitis model. Issue 7 (22nd March 2022) - He, Ying; Peng, Xie; Liu, Yang; Wu, Qing; Zhou, Qiang; Huang, Yingyan; Liu, Shiya; Hu, Liang; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; et al.
Abstract : Long-term maternal intake of inulin exacerbated the colonic damage and inflammation in DSS-induced offspring rats, associated with the decreased level of acetate and altered intestinal microbiota in colon. Abstract : This study aimed to investigate the effects of long-term maternal intake of inulin on intestinal morphology, permeability, inflammation and microbiota of offspring rats treated with dextran sulfate sodium (DSS). Sixteen female adult Sprague-Dawley rats were assigned to two groups receiving the fiber-free diet (FFD) or inulin diet (INU, 5% inulin) for three parities. The offspring weaned rats (third-parity) were fed with the same diet for four weeks until receiving 6% DSS for 7 days; the four groups were as follows: FFD, FFD + DSS, INU and INU + DSS. The results showed that maternal intake of inulin increased the histopathology score and activity of diamine oxidase (DAO) in serum, and the highest histopathology scores and activity of DAO were observed in INU + DSS rats. Maternal intake of inulin increased the activity of myeloperoxidase (MPO), mRNA expressions of inflammatory factors and protein expression of IL-1β in colonic tissues. Likewise, INU + DSS rats had the highest activity of MPO and mRNA expressions of inflammatory factors in colonic tissues. Maternal intake of inulin increased the abundances of Bacteroidetes, Bacteroides and Parasutterella, which were the highest enriched in INU + DSS rats. The level of acetate in the colonic digesta of INU + DSS rats was lower than that in FFD and INU rats. These results indicated that long-term maternal intake of inulin exacerbated the intestinal damage and inflammation of DSS-induced offspring rats, associated with the decreased level of acetate and altered intestinal microbiota.